Foreign Language Speaking Anxiety: Speaking Anxiety Levels and Factors among Tenth Grade Students - Wulandari, Ayunda; Siregar, Masitowarni; Husein, Rahmad (Jurnal Bahasa dan Sastra, 2024)
Language proficiency, particularly in English, is pivotal for students in Indonesia, yet many encounter Foreign Language Speaking Anxiety (FLSA) when required to speak English. This study examines FLSA among tenth-grade students, identifying varying anxiety levels. Most students fell into the moderate anxiety category, indicating that a significant portion experiences a moderate level of anxiety when speaking in a foreign language. A smaller but notable group of students reported high levels of anxiety, suggesting they face significant challenges due to their high anxiety levels. Internal factors contributing to anxiety include low proficiency, lack of practice, and fear of errors, while external factors encompass negative evaluations and social scrutiny. Additional factors identified include anxiety from recording and past negative experiences. Insights from Horwitz, MacIntyre, and Gardner's anxiety frameworks guide the study, emphasizing the complex interplay of cognitive, affective, and environmental factors. Data from questionnaires and interviews underscore the pervasive nature of speaking anxiety and highlight the need for supportive learning environments to alleviate anxiety and enhance language learning outcomes.